2017
DOI: 10.5114/jcb.2017.70731
|View full text |Cite
|
Sign up to set email alerts
|

What pelvic radiation disease symptoms are experienced by patients receiving external beam radiotherapy and a high-dose-rate brachytherapy boost for prostate cancer?

Abstract: PurposeResearch describing proctitis or pelvic radiation disease symptoms of prostate cancer patients one year after external beam radiotherapy (EBRT) plus high-dose-rate (HDR) brachytherapy is limited. This study aimed to assess prostate cancer patients’ pelvic radiation disease symptoms from baseline to 12 months post-radiotherapy.Material and methodsMen with prostate cancer referred for EBRT and HDR brachytherapy were recruited. Patients’ age, diagnosis, staging, PSA, past medical history, and treatment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…In the present study, patients with prostate cancer reported a high incidence of various urinary symptoms, such as acute toxicity due to IMRT, and exhibited adaptable self‐care actions so they could maintain daily activities. Our findings correspond with those of previous studies . Participants in the present study preferred to use public transport services (82.8%), providing easy access to restrooms for better self‐care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, patients with prostate cancer reported a high incidence of various urinary symptoms, such as acute toxicity due to IMRT, and exhibited adaptable self‐care actions so they could maintain daily activities. Our findings correspond with those of previous studies . Participants in the present study preferred to use public transport services (82.8%), providing easy access to restrooms for better self‐care.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study correspond to those of previous reports focusing on patients with prostate cancer during and after IMRT, in which patients undergoing IMRT for prostate cancer developed symptoms after radiotherapy . Furthermore, urinary symptoms and QoL changed during and after IMRT.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, this group was found to have a longer time to distant metastasis compared to the EBRT and ADT and radical prostatectomy groups. Moreover, acceptable toxicity rates have been shown using this approach [ 20 , 21 ]. These results have led to a push for combination treatment in those with NCCN high-risk prostate cancer, along with select intermediate risk patients.…”
Section: Discussionmentioning
confidence: 99%